2005
DOI: 10.1080/02699050410001720149
|View full text |Cite
|
Sign up to set email alerts
|

Life satisfaction and disability after severe traumatic brain injury

Abstract: Life satisfaction is not linearly related to disability after severe TBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
55
2
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(70 citation statements)
references
References 35 publications
7
55
2
6
Order By: Relevance
“…One drawback of the dichotomy is that it does not take into consideration the patient's perception of life satisfaction, which is crucial and cannot simply be equated with independent function 51 : studies have shown that self-reported quality of life can be good in the face of severe disability [52][53][54] and that the factors most strongly associated with disability outcomes are emotional rather than physical 4,55 .…”
Section: [H1] Criticismsmentioning
confidence: 99%
“…One drawback of the dichotomy is that it does not take into consideration the patient's perception of life satisfaction, which is crucial and cannot simply be equated with independent function 51 : studies have shown that self-reported quality of life can be good in the face of severe disability [52][53][54] and that the factors most strongly associated with disability outcomes are emotional rather than physical 4,55 .…”
Section: [H1] Criticismsmentioning
confidence: 99%
“…Underhill et al (2003) found that decreased life satisfaction was significantly associated with a diagnosis of depression among individuals who sustained a TBI at 24, 48, and 60 months after injury. Mailhan et al (2005), however, found that depression itself was not sufficient to directly explain all aspects of life satisfaction.…”
mentioning
confidence: 99%
“…The prediction of adjustment and well-being following traumatic injury is essential to the development of meaningful psychological and medical interventions and informed health policy, especially when considering health-related life satisfaction as a relevant outcome measure (Mailhan, Azouvi, & Dazord, 2005). Patient-oriented outcomes should be a priority for researchers, clinicians, and policy makers in order to improve health care and to promote individual quality of life (Kaplan, 1994;Kaplan & Frosch, 2005).…”
mentioning
confidence: 99%
“…Vários estudos têm revelado que as pessoas com LCA reportam níveis de QdV mais baixos do que a população em geral (Gordon et al, 2006;Jacobsson, Westerberg, & Lexell, 2010;Man et al, 2004;Nestvold & Stavem, 2009;Teasdale & Engberg, 2005), sendo evidente a necessidade de a reabilitação neuropsicológica promover a reintegração social e vocacional, de forma a aumentar a QdV dos indivíduos (Tomberg, Toomela, Pulver, & Tikk, 2005). O bem-estar após LCA parece ser determinado por uma grande variedade de fatores como o grau de autonomia , o estado emocional (Corrigan, Smith, & Granger, 1998;Koskinen, 1998), a capacidade física (Chandrashekar & Benshoff, 2007;Mailhan et al, 2005), o nível de participação social na comunidade (Pierce & Hanks, 2006) e o regresso ao emprego (Tomberg, Toomela, Ennok, & Tikk, 2007). Vários autores tentaram estudar de forma mais aprofundada a relação entre as características da lesão cerebral (Azouvi, Dufossé, Mailhan, & Dazord, 2005;Mailhan et al, 2005;Man et al, 2004;Nestvold & Stavem, 2009;Teasdale & Engberg, 2005), variáveis sociodemográficas Teasdale & Engberg, 2005) e psicossociais (Man et al, 2004;Tomberg et al, 2007;Tsaousides et al, 2009) e a avaliação da QdV, por parte dos indiví-duos.…”
Section: Impactos Da Reabilitação Neuropsicológica Na Qdvunclassified